2020
DOI: 10.1002/jlb.3ma0520-582r
|View full text |Cite
|
Sign up to set email alerts
|

Aloe emodin relieves Ang II-induced endothelial junction dysfunction via promoting ubiquitination mediated NLRP3 inflammasome inactivation

Abstract: Recent studies have revealed that aloe emodin (AE), a natural compound from the root and rhizome of Rheum palmatum L., exhibits significant pharmacologic activities. However, the pharmacologic relevance of the compound, particularly for cardiovascular disease, remains largely unknown. Here, we hypothesized that AE could improve endothelial junction dysfunction through inhibiting the activation of NOD-like receptor family pyrin domain containing-3 (NLRP3) inflammasome regulated by NLRP3 ubiquitination, and ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Yu et al (2019) findings indicated that AE can protect against myocardial infarction via the upregulation of miR-133, inhibition of ROS production and suppression of caspase-3 apoptotic signaling pathway. Zhang et al (2020) results revealed that inhibiting the activation of NLRP3 inflammasome and reducing the release of HMGB1 by promoting NLRP3 ubiquitination, thereby restoring the endothelial tight junction proteins and permeability, which indicated that AE exhibited immense potential therapeutic value in hypertensionrelated cardiovascular disease and the development of innovative drugs ( Table 3).…”
Section: Emodin Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al (2019) findings indicated that AE can protect against myocardial infarction via the upregulation of miR-133, inhibition of ROS production and suppression of caspase-3 apoptotic signaling pathway. Zhang et al (2020) results revealed that inhibiting the activation of NLRP3 inflammasome and reducing the release of HMGB1 by promoting NLRP3 ubiquitination, thereby restoring the endothelial tight junction proteins and permeability, which indicated that AE exhibited immense potential therapeutic value in hypertensionrelated cardiovascular disease and the development of innovative drugs ( Table 3).…”
Section: Emodin Derivativesmentioning
confidence: 99%
“…Inhibits NLRP3 inflammasome activation and decreases the release of HMGB1 by promoting NLRP3 ubiquitination, and thus restoring the endothelial tight junction proteins and permeability (Zhang et al, 2020)…”
Section: Fundingmentioning
confidence: 99%
“…In line with other ndings, our results showed the NLRP3 in ammasome in AMs was signi cantly activated both in NaT-AP rats and CER + LPS-AP mice. Emerging evidence showed that emodin had an inhibitory effect on the activation of NLRP3 in ammasome in myocardial injury combined with cardiovascular dysfunction [38,40,41]. Importantly, the administration of emodin and AYC markedly inhibited AP-associated activation of NLRP3 in ammasome in AMs, which was supported by downregulated expression of NLRP3, ASC, and Caspase1 p10.…”
Section: Discussionmentioning
confidence: 96%
“…In line with other findings, our results showed the NLRP3 inflammasome in AMs was significantly activated both in NaT-AP rats and CER+LPS-AP mice. Emerging evidence showed that emodin had an inhibitory effect on the activation of NLRP3 inflammasome in myocardial injury combined with cardiovascular dysfunction ( Ye et al, 2019 ; Zhang et al, 2020 ; Dai et al, 2021 ). In addition, Emodin could attenuate LPS-induced ALI through regulating the NLRP3 inflammasome-dependent pyroptosis signaling pathway ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%